Hydrodynamic instabilities - Charru, Francois (Cambridge texts in applied mathematics ;, 2011)
"The instability of fluids is a key topic in classical fluid mechanics because it has huge repercussions for applied disciplines such as chemical engineering, hydraulics, aeronautics and meteorology. This modern introduction is written for any student, researcher or practitioner working in the area, for whom an understanding of hydrodynamic instabilities is essential. Based on a decade's experience of teaching postgraduate students in fluid dynamics, this book brings the subject to life by emphasizing the physical mechanisms involved. The theory of dynamics provides the basic structure of the exposition and, wherever possible, Charru discusses the phenomena in terms of characteristic scales and dimensional analysis. Asymptotic methods also play an important role. The book includes numerous experimental studies, with references to videos and multimedia material, as well as over 150 exercises which introduce the reader to new problems"--